Realising the human development promise in dual VET - Vanderhoven, Ellen [Verfasser]; Fontdevila, Clara [Verfasser]; Langthaler, Margarita [Verfasser]; Valiente, Oscar [Verfasser]; Hermann, Ralf [Verfasser]; Marković, Jasminka [Verfasser]; Sethwala, Sadaf [Verfasser]; Maitra, Saikat [Verfasser]; Calderón, Eduardo [Verfasser] (My University, 2024)
"Despite growing consensus around the need for a more holisticvision of development, realising the human development potentialof educational interventions has proven a challenging task. ThisForum grapples with how these tensions manifest in the interna-tional transfer of dual models of Vocational Education and Training(dVET) to low- and middle-income countries. While dVET has gainedglobal currency, its developmental potential has been primarilyframed in economic terms. Conversely, its alignment with humandevelopment remains an abstract possibility and is often notreflected in the policy design of dVET transfer attempts.Each contribution to this Forum probes a different facet of thesetensions, exploring how dVET can be calibrated in different con-texts to realise its human development potential. Taking a practice-led approach and featuring representatives from cooperation agen-cies, consultancy groups, and research organisations, this piececontributes to ongoing debates about the possibility of effectivelyintegrating human development thinking into education policy." (BIBB-Doku, author's abstract)
Keywords: S 1.3.1 Ausbildung im Dualen System; 370; 300; Duales System; Berufsbildungssystem; Einkommen; Industrieländer; Schwellenländer; Bildungstransfer; Persönlichkeitsentwicklung; Rechtliche Regelungen